(untitled) (Colombia Medica, 2023)
Background Among the chronic myeloproliferative neoplasms (MPNs) not associated with BCR-ABL mutations are polycythemia vera, primary myelofibrosis, and essential thrombocythemia. These diseases are caused by gene mutations, such as the JAK2, MPL, and CALR genes, which regulate the JAK-STAT signaling pathway. Objective This study aimed to establish the frequencies of mutations in the JAK2, MPL, and CALR genes in Colombian patients with a negative clinical diagnosis of BCR-ABL chronic myeloproliferative neoplasms. Methods The JAK2 V617F and MPL W515K mutations and deletions or insertions in exon 9 of the CALR gene were analyzed in 52 Colombian patients with polycythemia vera, primary myelofibrosis, and essential thrombocythemia. Results The JAK2V617F mutation was carried by 51.9% of the patients, the CALR mutation by 23%, and the MPL mutation by 3.8%; 23% were triple-negative for the mutations analyzed. Six mutation types in CALR were identified in these neoplasms, one of which has not been previously reported. Additionally, one patient presented a double mutation in the CALR and JAK2 genes. Regarding the hematological results for the mutations, significant differences were found in the hemoglobin level, hematocrit level, and platelet count among the three neoplasms. Conclusion Thus, this study demonstrates the importance of the molecular characterization of the JAK2, CALR and MPL mutations in Colombian patients (the genetic context of which remains unclear in the abovementioned neoplasms) to achieve an accurate diagnosis, a good prognosis, adequate management, and patient survival.